PEMBERLAKUAN TEORI-TEORI HUKUM ISLAM DI INDONESIA - Farid, M; Panjaitan, Budi Sastra; Lubis, Fauziah (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2024)
Before the introduction of Islamic law, the Indonesian people adhered to customary law which had various systems and was very diverse in nature. In reality, the Islamic religion has had a big influence on the lives of Indonesian people to this day. Apart from that, the majority of the Indonesian population adheres to Islam, so it is natural that Islamic law always colors national law in Indonesia. The aim of this research is to find out the history of the implementation of Islamic law in Indonesia and the role of Islamic law in the development of national law in Indonesia using library research methods. The conclusion of this research is that Islamic law entered Indonesia at the same time as Islam entered Indonesia, which according to some circles began in the VII or VIII century AD. Meanwhile, Western law was only introduced by the VOC at the beginning of the seventeenth century AD and in the development of Indonesian national law, religious law ( Islamic law) is the most dominant basis, where Islamic law plays a very important role in shaping Indonesian human behavior. Therefore, Islamic law is an absolute element for the development of Indonesian national law. Keywords: History of Islamic Law, Theory of Islamic Law, reception a complex